Innovative Learning Strategies for Islamic Religious Education Based on Merdeka Belajar Curriculum in Vocational High Schools - Hosaini Hosaini; Mujamil Qomar; Agus Zaenul Fitri; Akhyak Akhyak; Kojin Kojin (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2024)
Innovative learning strategies for Islamic Religious Education are needed to improve cognitive abilities, including analysis, application, creation, presentation, and implementation; affective abilities, including appreciation and organization or characterization; and psychomotor abilities, with the perception of the Qur'an and Hadith, which can enrich the vocational needs of students. This qualitative case study research aims to describe and analyze innovative learning strategies for Islamic Religious Education at Mambaul Ulum Vocational High School based on the Merdeka Belajar curriculum. Data collection through interviews, observations, and documentation. Testing the validity of the collected data through triangulation, expert discussions, and member checking. Data analysis using the Miles, Huberman, and Saldana methods with data condensation, data presentation, and conclusion. The study showed that the Islamic Religious Education teachers implemented three innovative learning strategies. First, problem-based learning integrates religious concepts with real issues to develop cognitive, affective, and psychomotor abilities. Second, inquiry-based learning through independent investigation and applying religious concepts in everyday life to deepen understanding. Third, flipped classroom combines independent learning at home with classroom discussion activities. Applying three innovative learning strategies has an impact on increasing learning motivation, knowledge of worship, and critical thinking skills. The value of this research lies in the application of learning strategies that connect religious concepts with actual practices to improve the quality of learning in vocational environments. The research findings strengthen constructivism through problem-based, inquiry-based, and flipped classroom theory by showing that active, collaborative, and interactive learning improves understanding and application of learning materials.